Woven face mask made from CoolMax fibres with three layers (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
In this research, ten fabric samples of CoolMax have been produced for preparing reusable face masks. The first group of five woven fabric samples has been produced with different fabric structures (plain weave 1/1, basket weave in warp direction, basket weave in both directions, satin 8, and twill 3/1) with both warp and weft yarns having 750 twists/m. The other group of five woven fabric samples is produced with the same fabric structures but by using 850 twists/m for warp and weft. The plain weave 1/1 fabric is treated with a water-repellent finish. The fabric properties, such as anti-bacterial, moisture, and air permeability, have been evaluated. It is observed that the fabric samples produced from CoolMax with twill, basket weave, and satin would be suitable for the inner and middle layer of the face mask, as they absorb droplets, and liquids and prevent bacteria, while the treated plain weave 1/1 fabric with water-repellent finish can be used for the outer layer. The woven face mask with three layers has been evaluated by objective and subjective methods, and the results show that the air permeability is 15.8 cm3/cm2/s, which is good in terms of breathability as compared to a disposable face mask, and withstand 25 cycles of washing for anti-bacterial property. The suggested woven face mask with three layers can reducethe spreading of the infection of COVID-19.